2017
DOI: 10.1007/s10584-017-2010-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change vulnerability assessment of forests in the Southwest USA

Abstract: Climate change effects are already apparent in some Southwestern US forests and are expected to intensify in the coming decades, via direct (temperature, precipitation) and indirect (fire, pests, pathogens) stressors. We grouped Southwestern forests into ten major types to assess their climate exposure by 2070 using two global climate models (GCMs) and two emission scenarios representing wetter or drier conditions and current or lowered emission levels. We estimate future climate exposure over forests covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 48 publications
1
53
1
Order By: Relevance
“…Previous studies have indicated a high level of climate change exposure in the foothills of CA (Thorne et al, 2017(Thorne et al, , 2018 2015). Other dynamic vegetation model simulations indicate contracting needle leaf evergreen forest cover in some areas we identify as having low drought vulnerability (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated a high level of climate change exposure in the foothills of CA (Thorne et al, 2017(Thorne et al, , 2018 2015). Other dynamic vegetation model simulations indicate contracting needle leaf evergreen forest cover in some areas we identify as having low drought vulnerability (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…, Thorne et al. ). This is particularly the case in the Southwest where several major temperate ecosystem types find their southernmost limits in North America (Brown et al.…”
Section: Introductionmentioning
confidence: 99%
“…), or have relatively coarse thematic or spatial outputs (>1:1,000,000 map scale) that are useful for broad policy and strategy but may be too general for subregional applications (Thorne et al. ). For these reasons, we chose an approach that would generate a regional assessment of increased spatial and thematic detail to convey vulnerability to future climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEA approach integrates the distribution of a vegetation type, typically derived from remote sensing, with mapped current climate and projected future climate conditions to determine the climate envelope of that type and assesses the level of climate change for each pixel of that type under future conditions (Thorne, Boynton, Holguin, Stewart, & Bjorkman, 2016;Thorne, Choe, Boynton, et al, 2017;Thorne, Choe, Stine, et al, 2017). CEA differs from climate impact approaches that predict potential range or movement, such as species distribution models, in that CEA is an in situ approach that predicts the climatic shifts within a set area between time periods; it does not predict where species will shift in order to maintain an optimal climate envelope (e.g., Phillips, Anderson, & Schapire, 2006;Thorne et al, 2013), nor does it predict where or how fast a given set of climatic conditions will move (i.e., climate change velocity; Ackerly et al, 2010;Dobrowski & Parks, 2016).…”
Section: Introductionmentioning
confidence: 99%